Fabrication of hierarchically organized nanocomposites of Ba/alginate/carboxymethylcellulose/graphene oxide/Au nanoparticles and their catalytic efficiency in o-nitroaniline reduction. (15th October 2015) - Thomas, Molly; Naikoo, Gowhar Ahmad; Sheikh, Mehraj Ud Din; Bano, Mustri; Khan, Farid
Abstract : Efficient nanocomposite hydrogel synthesis by an environmentally benign approach for the reduction of o -nitroaniline to 1, 2-benzenediamine using NaBH4 . Abstract : Composite gels of Ba/alginate(Alg)/carboxymethyl cellulose (CMC) were prepared by a dissipative convective process. Graphene oxide (GO) and Au nanoparticle (Au-NPs) were successfully encapsulated into the polysaccharide matrix. The resulting composite gels were characterized by Fourier transform infrared (FTIR) spectrometry, Raman spectroscopy, powder X-ray diffraction (PXRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The rheological and mechanical behaviors of the composite gels were also investigated. The composite gels were tested for the reduction of o -nitroaniline ( o -NA), to 1, 2-benzenediamine in the presence of NaBH4 . Ba/Alg/CMC/GO/Au composite gels reduce o -NA within 3 min with a rate constant of 0.45 s −1 and the composite can be recycled for up to 4 successive cycles.